Female-biased sex ratios and delayed puberty in two fish species with different Ecologies in an Anthropogenically affected urban lake - Ashrafi, Roghaieh; Westermark, Ari; Leppänen, Matti T.; Vehniäinen, Eeva-Riikka (Elsevier, 2025)
In aquatic ecosystems, endocrine-disrupting compounds (EDCs) pose a growing concern for their potential adverse effects on fish reproduction and development. In lake Pyhäjärvi, located in the urban boreal region of Tampere, Finland, a significant number of sexually immature pikeperch (Sander lucioperca) individuals have been identified in size and age categories that are expected to be sexually mature. To explore if this phenomenon is attributed to estrogenic endocrine disruption, we conducted a comprehensive study comparing fish from lake Pyhäjärvi with those from a nearby reference lake, lake Näsijärvi. Roach (Rutilus rutilus), known for its susceptibility to EDCs, was also included for comparison. We examined various parameters in both pikeperch and roach, including size, condition factor, age, reproductive indicators, biometric indices and gonadal histology. We also assessed liver vitellogenin mRNA levels and genetic sex in roach, and measured estrogen levels in lake waters and wastewater treatment plant effluents. Results revealed that approximately one-third of fish in both species exhibited sexual immaturity in lake Pyhäjärvi, with a female-biased sex ratio. Surprisingly, we found no signs of estrogenic endocrine disruption, indicated by the absence of intersex fish in both species. Furthermore, vitellogenin levels in roach closely resembled those in the reference lake. Estrogens were undetectable in the lake waters, suggesting that factors other than estrogenic EDCs, including other potential endocrine disruptors such as PCBs or heavy metals, may be influencing delayed sexual maturity and skewed sex ratios. Further inquiry is needed to pinpoint these underlying causes. Our study provides essential baseline information on fish sexual development in lake Pyhäjärvi, emphasizing the need for ongoing monitoring and research to understand delayed sexual maturity and biased sex ratios. This is vital given the increasing concern about EDC impacts on aquatic ecosystems and the necessity for effective management strategies to protect these ecosystems' health and integrity.